Heritability of attention‐deficit hyperactivity disorder in adults. Issue 6 (30th June 2015) - Brikell, Isabell; Kuja‐Halkola, Ralf; Larsson, Henrik
Abstract : Attention‐deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder. Symptoms often persist into adulthood, with a prevalence of 2.5–5% in adult populations. Twin studies in childhood consistently report high heritabilities of 70–80%, while studies in adult samples show only moderate heritability of 30–40% when estimated from self‐ratings. This review summarizes the available research on the heritability of ADHD in adults. Three key findings are outlined: (i) self‐ratings lead to relatively low heritability estimates of ADHD, independent of age and whether ratings refer to current or retrospective symptoms; (ii) studies relying on different informants to rate each twin within a pair (i.e., self‐ratings and different parents/teachers rating each twin in a pair) consistently yield lower heritability estimates than studies relying on ratings from a single informant; (iii) studies using cross‐informant data via either combined parent and self‐ratings or clinical diagnoses information suggest that the heritability of ADHD in adults could be as high as 70–80%. Together, the reviewed studies suggest that the previously reported low heritability of ADHD in adults is unlikely to reflect a true developmental change. Instead, the drop in heritability is better explained by rater effects related to a switch from using one rater for both twins in a pair (parent/teacher) in childhood, to relying on self‐ratings (where each twin rates themselves) of ADHD symptoms in adulthood. When rater effects are addressed using cross‐informant approaches, the heritability of ADHD in adults appears to be comparable to the heritability of ADHD in childhood. © 2015 Wiley Periodicals, Inc.